Evolution of a Yeast With Industrial Background Under Winemaking Conditions Leads to Diploidization and Chromosomal Copy Number Variation - Mangado, Ana; Morales, Pilar; Gonzalez, Ramon; Tronchoni, Jordi (Frontiers in Microbiology, 2018)
Industrial wine yeast strains show genome particularities, with strains showing polyploid genomes or chromosome copy number variations, being easier to identify. Although these genomic structures have classically been considered transitory steps in the genomic adaptation to new environmental conditions, they may be more stable than thought. These yeasts are highly specialized strains able to cope with the different stresses associated with the fermentation process, from the high osmolarity to the final ethanol content. In this work, we use adaptive laboratory evolution, focusing on the initial steps of the fermentation process, where growth rate is maximum, to provide new insights into the role of the different genomic and chromosomic rearrangements that occur during adaptation to wine conditions, and providing an understanding of the chronology of the different evolutionary steps.